Dissociation of Prediction from Conscious Perception. (October 2014) - Vetter, Petra; Sanders, Lia L O; Muckli, Lars
The framework of predictive coding offers a parsimonious explanation for many perceptual phenomena. According to this framework, perception of the outer world is created by the comparison of incoming sensory information with an internal predictive model based on previous experience and context. However, it is unclear whether the predicted percept needs to enter conscious awareness for the internal predictive model to be effective. Here we used an apparent motion paradigm to show that while prediction and conscious awareness of a predicted percept may coincide, a dissociation can be observed. When sensory information provides reliable input for the internal predictive model, the predicted percept does not have to be consciously perceived for successful prediction. However, when sensory input is ambiguous, conscious awareness helps the prediction to take effect.